Tunable two-dimensional interfacial coupling in molecular heterostructures - Beibei Xu; Himanshu Chakraborty; Vivek K. Yadav; Zhuolei Zhang; Michael L. Klein; Shenqiang Ren (Nature Communications, 2017)
Two-dimensional van der Waals heterostructures are of interest due to their unique interlayer coupling and optoelectronic properties. Here authors develop a Langmuir-Blodgett method to organize charge transfer molecular heterostructures with externally tunable conductance and capacitance and broadband photoresponse.